1989
DOI: 10.1021/ja00197a042
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidation mechanisms of uric acid

Abstract: One-electron oxidation of uric acid generates the urate radical, which was studied in aqueous solution by pulse radiolysis and oxygen-uptake measurements. Acid-base properties of the uric acid radical were determined, i.e., p£al = 3.1 ± 0.1 and pXa2 = 9.5 ± 0.1. The reaction of the radical with oxygen was too slow to be measured, k < 10~2 dm3 mol-1 s'1. The one-electron-redox potential vs NHE, £7 = 0.59 V, was derived from the pH dependence of the redox potential, which was fitted through the values measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
190
0
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(199 citation statements)
references
References 0 publications
5
190
0
4
Order By: Relevance
“…29 Uric acid is widely distributed in the body in relatively high concentrations and is an efficient scavenger of hydroxyl radicals, superoxides and singlet oxygen, and can chelate transition metals. 30 It contributes up to 60% of the TAC in healthy subjects. 31 Uric acid levels are frequently elevated in hypertensive patients, as was the case in our subjects.…”
Section: Discussionmentioning
confidence: 99%
“…29 Uric acid is widely distributed in the body in relatively high concentrations and is an efficient scavenger of hydroxyl radicals, superoxides and singlet oxygen, and can chelate transition metals. 30 It contributes up to 60% of the TAC in healthy subjects. 31 Uric acid levels are frequently elevated in hypertensive patients, as was the case in our subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about the beneficial effects of uric acid. Uric acid may function as a powerful antioxidant, and possibly one of the most important antioxidants in plasma [26][27][28] . Watanabe et al 23 has suggested that hyperuricemia maintains blood pressure during low salt intake environments, which may have provided a survival advantage during the course of primate evolution.…”
Section: Protective (Antioxidant) Functions Of Uric Acidmentioning
confidence: 99%
“…A negative prognostic factor for survival in heart failure patients is still controversial whether high uric acid is a compensatory attempt to counteract increased oxidative stress, an independent cause of CVD, or just a condition associated with other well-established risk factors such as hypertension, diabetes, and an accelerated clinical evolution of the disease [26][27][28][29] . Some authors suggested that high UA levels may promote the hypertensive organ damage, exerting a deleterious effect on endothelial function.…”
Section: Uric Acid In Hypertension and Cardiovascular Disordersmentioning
confidence: 99%
“…168,169 Uric acid is an acid with a pK a1 value of 5.75 and a pK a2 of 9.8. Uric acid in plasma is mainly present as the urate monoanion 168,[170][171][172] and is considered to be the major antioxidant in human plasma. However, the low aqueous solubility of both uric acid and sodium urate carries a risk of precipitation of crystals of uric acid or sodium urate in tissue and joints.…”
Section: Introductionmentioning
confidence: 99%
“…179 Uric acid is generated in the gastrointestinal tract through the breakdown of purine bases from the diet. 169,170,174,183 Both serum and gastrointestinal levels of uric acid may thus be modulated by dietary factors and a high intake of red meat is traditionally considered a risk factor for hyperuricemia and diseases resulting from this condition. [174][175][176][177]184,185 A higher level of uric acid formed in the digestive tract during food digestion could, however, also have positive health effects, since uric acid could be important as a reductant of hypervalent meat pigments.…”
Section: Introductionmentioning
confidence: 99%